Responsivitas Pelayanan Publik Berbasis E-Government Dengan Inovasi Identitas Kependudukan Digital - Salamena, Allgreat Meidelia Clarista; Emanuel, Andi Wahju Rahardjo (Jurnal Teknik Informatika dan Sistem Informasi, 2024)
This study aims to analyze the service responsiveness at the Population and Civil Registration Office of Ambon City, particularly regarding the implementation of Digital Population Identity (DPI). Public service responsiveness is considered crucial in meeting society's expectations towards technological advancements. The research method applied is qualitative, with data collection through direct observation and interviews at the Population and Civil Registration Office of Ambon City. The research results are expected to provide insights into the service responsiveness of this institution towards the needs and expectations of the community. Thus, this research can offer insights into how the office can enhance its responsiveness to technological changes and societal demands.